Organophosphate poisoning : A review (Faculty of Medicine Universitas Indonesia, 2003)
Organophosphate pesticides are used extensively worldwide, and poisoning by these agents, particularly in developing nations is a public health problem. Organophosphorous nerve agents are still considered as potential threat in both military or terrorism situations. The mechanism of toxicity is the inhibition of acetylcholinesterase, resulting in accumulation of the neurotransmitter acetylcholine and continued stimulation of acetylcholine receptors both in central and peripheral nervous systems. Beside acute cholinergic crisis, organophosphates are capable of producing several subacute or chronic neurological syndromes. The well described intermediate syndrome (IMS) emerges 1-4 days after an apparently well treated cholinergic crisis. The standard treatment consists of reactivation of inhibited acetylcholinesterase with an oxime antidote (pralidoxime, obidoxime, HI-6 and Hlo7) and reversal of the biochemical effects of acetylcholine with atropine. The newer oximes HI-6 and Hlo& are much more suitable and efficacious acetylcholinesterase reactivator for severe acute nerve agent induced poisoning than currently used pralidoxime or obidoxime. Patients who receive treatment promptly usually recover from acute toxicity but may suffer from neurologic sequelae. (Med J Indones 2003; 12: 120-6) Keywords: poisoning, insecticide, organophosphate (OP), carbamates, acetylcholinesterase, oxime, pralidoxime, obidoxime, HI-6, HLo7